Preliminary study on immobilization of plant esterase on functionalized multi-walled carbon nanotubes (MWCNTs) for biosensor application - Abdullah, Nurul Awanis; Yusof, Faridah; Ahmad, Farah (2020)
The functionalization of multi-walled carbon nanotubes (MWCNTs) is extremely important to increases their solubility. This study reported the efficient functionalization of MWCNTs via acid treatment introducing carboxyl group at the side wall of MWCNTs by mixing the concentrated nitric and sulfuric acid. Plant esterase enzyme extracted from wheat flour called alpha naphthyl acetate esterase (ANAE) was immobilized onto functionalized MWCNTs via covalent attachment of amine group in ANAE and carboxyl group of functionalized MWCNTs. In order to characterize the functionalization of MWCNTs and immobilization of enzyme, Fourier transform infrared (FTIR) spectroscopy have been used to confirm the existence of these functional groups. The FTIR spectrums revealed that the several peaks formed at 1992.39, 2324.14, 2880.85 and 3029.51 cm-1 which can be assigned to the C=O symmetric stretching, O−H stretch from strongly hydrogen-bonded –COOH, H−C stretch modes of H−C=O in the carboxyl group, and O-H stretch from carboxyl groups (O=C−OH and C−OH) respectively. The immobilization of ANAE on functionalized MWCNTs confirmed by observation of the peak at 3646.81 cm-1 and 3850.91 cm-1 introduced the strong amide linkages between carboxylic acid groups and amine group on the MWCNTs. This proposed framework can be applied for fabrication of screen printed electrode as biosensor for detection of pesticide